2002
DOI: 10.3346/jkms.2002.17.3.423
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Calcium Pyrophosphate Dihydrate Crystal Deposition Disease Presenting as an Acute Polyarthritis

Abstract: A Case of Calcium Pyrophosphate Dihydrate Crystal Deposition Disease Presenting as an Acute PolyarthritisWe report a case of calcium pyrophosphate dihydrate crystal deposition disease (CPDD) presenting as an acute polyarthritis. A 66-yr-old woman was admitted with a 5-day history of fever and multiple joint pain including wrists, elbows, shoulders, knees, and ankles developed 5 days before admission. Her plain radiographs of wrists, elbows, shoulders, knees, and ankles showed chondrocalcinosis. The pubic symph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…La enfermedad por depósito de cristales de pirofosfato de calcio es una enfermedad heterogé-nea que se caracteriza por la presencia de cristales intraarticulares. Tiene tres presentaciones clásicas que consisten en sinovitis aguda (llamada también pseudogota, como en este caso), artritis crónica y condrocalcinosis asintomática 9 . La pseudogota es una causa poco común de fiebre y elevación de parámetros inflamatorios, sin embargo, es la causa más común de monoartritis en el adulto mayor 9 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La enfermedad por depósito de cristales de pirofosfato de calcio es una enfermedad heterogé-nea que se caracteriza por la presencia de cristales intraarticulares. Tiene tres presentaciones clásicas que consisten en sinovitis aguda (llamada también pseudogota, como en este caso), artritis crónica y condrocalcinosis asintomática 9 . La pseudogota es una causa poco común de fiebre y elevación de parámetros inflamatorios, sin embargo, es la causa más común de monoartritis en el adulto mayor 9 .…”
Section: Discussionunclassified
“…Tiene tres presentaciones clásicas que consisten en sinovitis aguda (llamada también pseudogota, como en este caso), artritis crónica y condrocalcinosis asintomática 9 . La pseudogota es una causa poco común de fiebre y elevación de parámetros inflamatorios, sin embargo, es la causa más común de monoartritis en el adulto mayor 9 . El término condrocalcinosis se utiliza para denominar a la calcificación del cartílago hialino y/o fibrocartílago evidenciada mediante una radiografía convencional [10][11][12] .…”
Section: Discussionunclassified
“…Acute crystal deposition arthritis is one of the common causes of acute monoarthritis. While Song et al 7 reported a case of CPPD crystal deposition disease presenting as an acute polyarthritis, concurrent attacks in more than one joint are unusual.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CRP level (24.3 mg/dl) in our patient (Case A) with pseudogout was quite high. A Korean female patient of calcium pyrophosphate dihydrate crystal deposition disease (CPDD) presenting as an acute polyarthritis also showed significantly elevated serum CRP levels (18.8 mg/dl) 11. However, it is too difficult to differentiate CPDD and CPDD + PMR from PMR, especially in elderly patients 12.…”
Section: Discussionmentioning
confidence: 99%